Resistance in bacteria and indirect beta-lactamase detection in E. coli isolated from Culex pipiens detected by matrix-assisted laser desorption ionization time of flight mass spectrometry. Issue 1 (2nd January 2017) - Hleba, Lukáš; Kmeť, Vladimír; Tóth, Tomáš; Kačániová, Miroslava
ABSTRACT: The aim of this study was detections of antibiotic resistance and resistance mechanism in bacteria isolated from mosquitos ( Culex pipiens ) living near humans. Therefore, antibiotic resistance in bacteria isolated from Culex pipiens was investigated by disk diffusion test and MIC E-test in this study. MALDI-TOF mass spectrometry was used for detection of resistant mechanism. In this study, hydrolytic breakdown products after a few hours of incubation of the bacteria isolated from Culex pipiens were detected. Results show that enzymatic destruction of ampicillin by beta-lactamases is able to be detected by MALDI-TOF mass spectrometry from wild strains of potential pathogens. The MALDI-TOF mass spectrometry is useful method for routine detection of beta-lactamases resistant mechanism, but overnight incubation of pure culture is necessary. The results are important for proper and fast intervention to limit the spread of beta-lactamase-producing wild bacteria and provide information for appropriate initial therapy of the infections caused by these microbes.